A Luenberger-type observer for the AM2 model. (August 2015) - Didi, Ibtissem; Dib, Hacen; Cherki, Brahim
Abstract : Highlights: We designed a nonlinear observer for the AM2 model with linear errors. We proved that this observer is robust with a global convergence and adjustable speed. For large speed of convergence, we noticed that in a small time interval at the beginning, some variables can take erroneous values (<0). The quantity of methane produced by the system can be estimated from variables x 1 and x 2 which qualifies our observer as a software sensor for the methane. Abstract: In this paper, we deal with the problem of designing a new observer for bioreactor models. The main idea is to construct a nonlinear observer with linear errors, which has an adjustable and robust convergence. Simulation results are presented using a model of Chemostat and a model of an anaerobic digestion process for the treatment of wastewater.